Forgotten Poet Nihadi From Sarajevo: Persian Ghazals From Berlin Manuscript of Divan - Gačanin, Sabaheta (Prilozi za orijentalnu filologiju, 2017)
As a poet from the early period, Mustafa Karamusić Nihadi drew scholarly attention of our cultural researchers relatively late in comparison. Only fragmental and scatchy accounts were given in sources and literature on him and his Divan, the only surviving copy of which is preserved in Berlin; his poetics remain largely unstudied. The aim of this article is to offer an evaluation of his Persian ghazals as a befitting contributing to our history of cultural memory so not to forget what we must not forget. Each ghazal as a poetical and stylistic unit in its sophisticated divani form is a place of recollection which traditionally conveys abundant information about a several centuries long cultural community that was not only local but universal in its outlook, upholding cosmical values. It is always in the shade of mystical tendencies and imperative to remember and preserve universal human values as a pattern of transtemporal cultural memory.